The role of nursery school teachers in early intervention with children with signs of ASD - Perosa Saigh Jurdi, Andréa; Baptista da Silva, Carla Cilene; Ferreira Roque Costa, Daniella (Frontiers in Education, 2023)
In Brazil, daycare as a social and economic reality for many families is consolidated as a natural context for the child and complementary to the family, and places teachers as important partners within an integrated system that involves the care of children from zero to three years old in the promotion of their full development. The experiences lived in daycare are decisive and fundamental in the child development process, and teachers as agents of intervention must be alert to possible early signs of change in the child's development. However, the practices of Brazilian daycare teachers have been little investigated with regard to school inclusion. In this sense, this research aimed to investigate the experiences of daycare teachers with children who present risk signs for Autism Spectrum Disorder (ASD). This is a qualitative exploratory research, with the participation of 10 teachers from public daycare centers in a city in the state of São Paulo. The information was obtained through semistructured interviews that followed a script previously defined by the researchers. Data analysis was carried out using thematic content analysis. The results pointed out that the teachers' conceptions about development, permeated by their own ideas about education, care, family and society, imply directly in their practices with the child and in the conduction of the case to other spheres. It was possible to verify the protagonism of the teachers who have in their effective practices care and play as intervention strategies in their actions. Gaps emerged regarding the communication between education professionals and the articulation between education and health. We identified the need for consistent intersectoral actions that favor the development of children who show early signs of ASD and value the role of the teacher in this process, also promoting inclusive educational practices.